Enhanced Post-Ischemic Neurogenesis in Aging Rats - Tan, Yao-Fang; Preston, Edward; Wojtowicz, J. Martin (Frontiers in Neuroscience, 2010)
Hippocampal neurogenesis persists in adult mammals, but its rate declines dramatically with age. Evidence indicates that experimentally-reduced levels of neurogenesis (e.g. by irradiation) in young rats has profound influence on cognition as determined by learning and memory tests. In the present study we asked whether in middle-aged, 10-13 months old rats, cell production can be restored towards the level present in young rats. To manipulate neurogenesis we induced bilateral carotid occlusion with hypotension. This procedure is known to increase neurogenesis in young rats, presumably in a compensatory manner, but until now, has never been tested in aging rats. Cell production was measured at 10, 35 and 90 days after ischemia. The results indicate that neuronal proliferation and differentiation can be transiently restored in middle-aged rats. Furthermore, the effects are more pronounced in the dorsal as opposed to ventral hippocampus thus restoring the dorso-ventral gradient seen in younger rats. Our results support previous findings showing that some of the essential features of the age-dependent decline in neurogenesis are reversible. Thus, it may be possible to manipulate neurogenesis and improve learning and memory in old age.